The impact of school fruit tuck shops and school food policies on children's fruit consumption: a cluster randomised trial of schools in deprived areas. Issue 10 (15th May 2008) - Moore, L; Tapper, K
Abstract : Aims: To estimate the impact of school fruit tuck shops on children's consumption of fruit and sweet and savoury snacks. Design: Cluster randomised effectiveness trial with school as the unit of randomisation. Setting: 43 primary schools in deprived areas in south Wales and south-west England with a range of school food policies. Intervention: Schools operated fruit tuck shops throughout one academic year. Control schools did not do so. Measures: Repeated cross-sections of children aged 9–11 years completed a computerised 24-hour recall questionnaire at baseline (n = 1902) and at 1-year follow-up (n = 1924), when a brief questionnaire was also completed (n = 1976). Results: Approximately 70 000 fruits were sold in the 23 intervention schools over the year, equivalent to 0.06 fruits per student per day. Children in intervention schools were more likely to report eating fruit as a snack at school 'often' (OR 1.49, 95% CI 1.15 to 1.95). There were no significant differences in children's intake of fruit or other snacks. There was a significant interaction (p<0.02) between the intervention group and school food policy: where students were only allowed to bring fruit to school, fruit consumption was 0.37 portions per day (0.11 to 0.64) higher in intervention schools, compared to 0.14 portions (−0.30 to 0.58) where no food was allowed and −0.13 portions (−0.33 to 0.07) where there were no restrictions. Conclusions: In isolation, fruit tuck shops were not effective in changing children's snacking behaviour in schools. However, the results suggest that fruit tuck shops had a greater impact when reinforced by school policies restricting the types of foods students were allowed to bring to school.